Remote Assistance for Elderly to Find Hidden Objects in a Kitchen - Asghar, Zeeshan; Keranen, Niina; Yamamoto, Goshiro; Taketomi, Takafumi; Sandor, Christian; Kato, Hirokazu; Pulli, Petri (EAI Endorsed Transactions on Pervasive Health and Technology, 2017)
We present a design and preliminary evaluation of novel visual guidance of a remote assistive system for the elderly to find hidden objects in a kitchen. Our system has two essential functions; 1) to update a list and corresponding location information of objects concealed in a shelf with at all times, and 2) to display images and texts about the objects on the corresponding area of the door of the shelf. We aim to realize assistive visual guidance to elderly for overcoming the deficits of initiation, planning, attention and memory deficits while performing kitchen-based activities of daily living such as finding items for cooking. In this study, we focus on hidden objects because there is an increased possibility for the elderly with cognitive impairments to forget where and what the object is due to the non-visibility. The paper shows the prototype system that uses RFID and projection technology. We conducted a user study with twelve elderly participants to evaluate the usability of the system using the System Usability Scale (SUS). Additionally, we also investigate the acceptability of the system by applying the Unified Theory of Acceptance and Use of Technology (UTAUT). The results demonstrate that the elderly participants found the system useful and easy to use. Finally, we conclude that a remote assistive system can be used to assist elderly to storing and retrieving objects from cabinet and shelves during a kitchen task but need more studies to make the system more efficient and effective.